Study on Dynamic Characteristics of Automotive Shock Absorber System - M. S. M., Sani; M. M., Rahman; M. M., Noor; M. R. M., Rejab; K., Kadirgama (2008)
Shock absorber is one of important component in a vehicle suspension system. The shock control spring motion by damping energy from the spring. This paper was focused on the dynamic characteristics of an automotive shock absorber. The design of interchangeable shock absorber test rig was developed and fabricated for the dynamics measurement system. This test rig integrated with the computer systems to record the signal. An experiment was conducted to identify the stiffness and damping parameter for 850 cc and 1600 cc shock absorber. Simulation study was performed utilizing the COSMOS Motion software. It can be seen from the results that there is a good agreement between the experimental and simulated results in terms of stiffness and damping value except few discrepancy. The acquired results show that the range of discrepancy within 10%. The good range of stiffness of the passenger vehicle shock absorber is 20 N/mm to 60 N/mm while the damping of passenger vehicle shock absorber is 1 Ns/mm to 6 Ns/mm.